The Mental Workload Analysis on Female Educators During Covid-19 Pandemic Using Nasa-TLX Method - Andivas, Marulan; Harits, Dimaz; Wibowo, Agus Hindarto; Thoriq, Eaden Ahmed; Ghazali, Ihwan (Spektrum Industri, 2023)
The fate of women workers during the pandemic is quite worrying. The role of women's triple burden in these times is getting heavier. Mental workload is a multidimensional construct that demands attention, performance, and skills of workers according to their work environment. This study aims to find out the mental burden felt by female workers during the pandemic. The subjects of this study were female educators at the University of Balikpapan. Five subjects feel a Very high mental burden on work activities during a pandemic, namely subjects 06, 14, 19, 23, and 25. There are 18 subjects who feel a high mental burden including subjects 3, 4, 5, 7, 8, 10, 12, 13, 16, 17, 18, 20, 21, 26, 28, 29, 30, and 31. Then, 3 subjects felt a moderate mental load, and 2 subjects felt a low mental load. If average, then the mental workload of female educators at the University of Balikpapan is 56.623 categorized as high. This study also seeks to investigate the correlation between the perceived workload of the subjects and several factors including age, marital status, education level, address, family size, income, COVID-19 survivor status, and family members who are COVID-19 survivors. The result showed that the number of family members is the only significant factor that influences the mental workload.